Trauma and Spirituality: Faith Interacting with Counselors’ Sexual Violence Work - Waters, Mitchell (Counseling and values, 2025)
In this transcendental phenomenological study, the lived experiences of an international sample of 11 religiously and spiritually diverse counselors who work with survivors of sexual violence were examined. By collecting data with semi-structured interviews, the researchers identified three themes: 1) adverse psychological consequences, 2) intersecting identities, and 3) growth and resilience. The findings of this study highlight the complex nature of the roles that religion and spirituality play for counselors making meaning of their experiences.